The Concussion Challenge Assessment: Development and reliability of a novel gross motor assessment tool for paediatric concussion - Tanel, Michelle R.; Gupta, Christopher; Wilson, Katherine E.; Murphy, James; Wright, F. Virginia; Reed, Nick (Frontiers in Sports and Active Living, 2022)
Aims: To develop a gross motor performance clinical assessment tool, the Concussion Challenge Assessment (CCA), for pediatric concussion populations. Methods: An expert panel evaluated tasks from the Acquired Brain Injury Challenge Assessment to determine relevant tasks for a pediatric concussion population. These tasks were administered to a convenience sample of 854 healthy youth. An analysis of the response options for each task, considering task difficulty, was performed. The test-retest reliability of each task was considered to finalize the tool. Results: The Acquired Brain Injury Challenge Assessment was reduced to six tasks (three coordination, two speed and agility, one strength) to create the CCA. Population-specific 4-point response options were generated, which, upon examination of task difficulty, were revised as 5-point response sets to better capture performance differences. The test-retest reliability results led to acceptance of all six: three performance tasks and three exertion tasks. Conclusion: This development of the CCA is an important step in creating a gross motor performance assessment tool that can assist in determination of when a youth is able to safely return to activity following a concussion.